Adrenaline and nebulized salbutamol in acute asthma. Issue 7 (July 1984) - Turpeinen, M; Kuokkanen, J; Backman, A
Abstract : The effects of injected adrenaline and nebulized salbutamol on acute asthma were compared in 46 children. The results showed that salbutamol had a significantly better bronchodilatory effect than adrenaline. Nebulized salbutamol is recommended as a primary method of treatment of asthmatic attacks in childhood.